A biomimetic ion-crosslinked layered double hydroxide/alginate hybrid film. Issue 52 (27th June 2017) - Liang, Ben-liang; Wang, Jian-feng; Shu, Ying-qi; Yin, Peng-gang; Guo, Lin
Abstract : Inspired by the structure of nacre, a biomimetic Ca 2+ -crosslinked layered double hydroxide/alginate (LDH/ALG-Ca 2+ ) hybrid film is prepared, which exhibits excellent mechanical property and high transparency. Abstract : Natural nacre has an ordered layered arrangement of calcium carbonate platelets and ion-crosslinked protein, which enable it to achieve outstanding mechanical properties. Inspired by the relationship between structure and mechanical properties of natural nacre, we fabricate a Ca 2+ -crosslinked layered double hydroxide/alginate (LDH/ALG-Ca 2+ ) hybrid film through filtration of Ca 2+ -crosslinked LDH/ALG hybrid building blocks. The LDH nanoplatelets and alginate were alternately stacked giving an ordered layered structure, in which alginate was crosslinked by Ca 2+ . The effect of LDH content and Ca 2+ crosslinking on the microstructure and interfacial interaction of LDH/ALG-Ca 2+ hybrid films was studied systematically. The optimized nacre-like hybrid film exhibits good flexibility and high strength (194 MPa), superior to natural nacre. The ordered layered structure and small diameter of LDH give the hybrid film a high transparency of 74–94% in the visible light wavelength range.